Emphysematous pyelonephritis and hepatic hemangioma in a patient with diabetes mellitus case report and review of literature - Trillo Ramos, Miguel (2018)
ABSTRACT Emphysematous pyelonephritis is a serious infection of acute presentation, highly fatal due to septic complications. This infection is infrequent and usually affects uncontrolled diabetic women. The causative agents are the gas-producers coliforms and other uropathogenic enterobacteries.The infection usually has a high morbidity and mortality, which requires an early diagnosis and aggressive treatment. On the other hand, hepatic incidentalomas are considered lesions that are discovered in asymptomatic subjects. We describe the case of a 47-year-old patient with Diabetes Mellitus diagnosed 10 years ago, who developed acute emphysematous pyelonephritis caused by Escherichia coli BLEE positive. Diagnosis was confirmed by CT. An early and aggressive antibiotic treatment allowed complete resolution without the need for a surgical approach. Incidentally, a non-homogenous hypodense lesion was found in the liver, compatible with hepatic hemangioma. Key words: Emphysematous pyelonephritis; Diabetes mellitus; Hepatic hemangioma. (source: MeSH NLM) DOI:  10.25176/RFMH.v18.n3.1601